Kinetic Catalytic Spectrophotometric Determination of Thiocyanate Ion Using the Oxidation of Thionine by Bromate - Hashemian, Saeedeh; Reza Sheshabor, Masood; Amiri, Mohammad (Asian Journal of Chemistry, 2010)
A new and sensitive kinetic spectrometric method was developed for the determination of ultra free amounts of thiocyanate ion in water samples. The method is based on the inhibiting effect of thiocyanate ion on the oxidation of thionine by bromate in acidic medium. The reaction was monitored spectrophotometrically by 600 nm with a fixed-time method. The decrease in the absorbance of thionine is proportional to the concentration of thiocyanate ion in concentration range 2.0 × 10-4-2.0 × 10-3 M with a fixed time of 0.5-5 min from initiation of the reaction. The limit of detection is 0.048 ng/mL thiocyanate ion. The relative standard deviation of 0.3 and 1 ppm of thiocyanate ion were 2.13 and 1.36, respectively. The method was applied to the determination of thiocyanate ion in natural water.